Comparative Analysis of Soluble Proteins in Four Medicinal Aloe Species by Two-Dimensional Electrophoresis and MALDI-TOF-MS. (23rd November 2019) - Fan, Jiao-Jiao; Li, Chun-Hong; Hu, Guang; Tan, Cheng-Ning; Yang, Feng-Qing; Chen, Hua; Xia, Zhi-Ning
Abstract: Background: Aloe barbadensis Miller 1768, A. vera L. var . chinensis (Haw.) Berger 1908, A. ferox Miller 1768, and A. arborescens Miller 1768 are the most widely cultivated species of Aloe and are used in Asia along with 400 other Aloe species worldwide because of their potent and potential bioactivity. Objective: The objective was to analyze and compare the soluble proteins of four commonly used medicinal Aloe species. Methods: Aloe protein samples were obtained by TCA/acetone-saturated phenol-methanol/ammonium acetate combined extraction (phenol extraction), and then were analyzed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis and two-dimensional gel electrophoresis. Finally, the differentially expressed proteins of four Aloe species were identified by matrix-assisted laser desorption ionization–time-of-flight–MS analysis. Results: The phenol extraction method was the most suitable method for the protein extraction of Aloe . Fifty differentially expressed proteins in four Aloe species were successfully identified and divided into eight functional categories. Furthermore, Malate dehydrogenase and ran-binding protein in A. barbadensis, cytoskeletal-related protein tubulin in A. vera var . chinensis and auxin-induced protein PCNT-115 in A. arborescens are closely related to their morphological characteristics. Conclusions: There are differences in the soluble proteins of the four Aloe species. Those proteins, related to the difference of their morphology of Aloe, might be used to identify different species. Highlights: Fifty differentially expressed proteins in four medicinal Aloe species were identified, and these proteins were classified into eight categories according to their biological functions. Four special proteins closely related to the morphological characteristics of Aloe were found and might be used to identify these four Aloe species.